Evaluating the effect of tanning response to sun exposure on the risk of skin diseases through Mendelian randomization - Ping, Weidong; Zhao, Qiming; Ge, Shuhong; Wang, Xin; Li, Fei; Huang, Xiaoxiang (Frontiers in Genetics, 2022)
Background: Until now, the relevance of the tanning response to sun exposure and skin diseases has incomplete and inconsistent epidemiological observations. In this case, it is valuable to find out the causality of tanning response to sun exposure and skin diseases, and take a step further toward developing effective therapies as well as prevention methods. Methods: We investigated the causal effect of tanning response to sun exposure on 10 major skin diseases that have been studied in recent large-scale genome-wide association studies (GWASs). Significant independent genetic variants from large-scale GWAS on ease of skin tanning (N = 453,065) are selected as the effective instrumental variables (IVs). For each skin disease, we extracted the summary statistics of those IVs (or their proxies) from the corresponding skin disease-GWAS as the valid IVs. Mendelian randomization (MR) was further performed to evaluate the causal association of ease of skin tanning with each of the skin diseases using different statistical methods, including inverse-variance weighted (IVW), the weighted median, and MR-Egger. Sensitivity analysis was also conducted to evaluate the effect of horizontal pleiotropy and heterogeneity. Results: We observe significant associations between six skin diseases with tanning response to sun exposure with adjusted p-value derived by IVW less than 0.05 and with nominal p value less than 0.05 at the same time derived by either MR-Egger or weighted median. The six skin diseases include actinic keratosis (IVW FDR = 1.71E-40, MR Egger p-value = 3.46E-22), seborrhoeic keratosis (IVW FDR = 2.97E-4, MR Egger p-value = 1.06E-3), blepharochalasis (IVW FDR = 1.30E-3, MR Egger p-value = 2.91E-4), seborrhoeic dermatitis (IVW FDR = 1.29E-2, MR Egger p-value = 1.23E-2), malignant melanoma of skin (IVW FDR = 2.95E-2, MR Egger p-value = 1.91E-2), and freckles (IVW FDR = 2.95E-2, weighted median p-value = 1.02E-3). Interestingly, we find increased trends of developing all of the six skin diseases with increased tanning response to sun exposure (beta values are positive using IVW, MR-egger, and weighted median methods). We also replicate the association on three skin diseases using an independent outcome GWAS cohort, including malignant melanoma of the skin (replication IVW p-value = 2.13E-39), actinic keratosis (replication IVW p-value = 4.64E-32), and seborrhoeic keratosis (replication IVW p-value = 1.79E-3). Conclusion: Our observation shows that the tanning response to sun exposure is positively correlated with the development of skin diseases in people of European descent by Mendelian randomization studies. But randomized controlled trials are still needed to add proof to our observations.